The Nature of Contemporary Reality - Bratina, Boris R. (Collection of Papers of the Faculty of Philosophy in Priština, 2023)
Reality seems to have become a matter of ownership—everyone supposedly has the right to ‘their’ reality. In contrast, to this supposed freedom of acceptance, there is a ‘scientific’ interpretation of reality, which claims to be the only correct one in modern times. The text presented here wants to show not only the limitations of the ‘scientific’ interpretation, as a pure formalism, but especially that its ideological glosses cannot reveal the reality. Instead, they falsify it, not just as the success of theory, but as reality itself. This is especially visible in modern times. In that name, over a hundred years have passed since the theory suppresses subjectivity in the explanation of reality; philosophy at the level of the establishment has accepted this very task. However, it was not motivated only by theoretical reasons, but intentionally, as an imposition of the nature of reality and the idea of the human nature of subjectivity. Although the ‘primacy of the theoretical’ was promoted after Kant’s ‘primacy of the practical’, theory as a formalism manifested violence in its own understanding of reality and at the same time, after all the apologies, subjectivity was not accepted within it as the foundation of reality, but as a place of application of systemic results. The author shows that this procedure is possible as an action in reality, but that it is beyond his power to explain it. Finally, the author is in favour of reintroducing subjectivity into the theoretical structuring of reality, because its interpretation without subjectivity is as wrong as it is involved in the interests of subjectivity that are not subjectivity as subjectivity. They think that from the epistemological situation and diagnosis of modernity, it is possible to derive a theory that can take into account the essential nature of subjectivity in the interpretation of the nature of reality.
Keywords: reality; theory; subjectivity; science; structure; interpretation